Analysis of the adhesive damage for different shapes and types patchs in corroded plates with an inclined crack - Hayet Benzineb; Mohamed Berrahou; Mohamed Serier (Fracture and Structural Integrity)
In this study, the finite element method is used to analyze the effect of corrosion and the behavior of inclined cracks of an aluminum plate Al 2024 -T3 under thermomechanical loading. The effects of the inclination of the crack and the effect of temperature for different types and shapes of adhesives are highlighted. The results obtained show the increase of the crack inclination leads to a decrease of the damaged area and the damaged area ratio of the adhesive. In addition, the ratio DR increases with increasing temperature variation ?T. The best performing patch shape that gave interesting results during this analysis is the circular and for type the Boron/epoxy is the best.